2017
DOI: 10.1103/physrevlett.118.130501
|View full text |Cite
|
Sign up to set email alerts
|

Direct Probe of Topological Invariants Using Bloch Oscillating Quantum Walks

Abstract: The topology of a single-particle band structure plays a fundamental role in understanding a multitude of physical phenomena. Motivated by the connection between quantum walks and such topological band structures, we demonstrate that a simple time-dependent, Bloch-oscillating quantum walk enables the direct measurement of topological invariants. We consider two classes of one-dimensional quantum walks and connect the global phase imprinted on the walker with its refocusing behavior. By disentangling the dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 42 publications
1
81
0
Order By: Relevance
“…Here |Φ h (q) denotes the wavefunction of a hole excitation at quasimomentum q while |ψ I describes the wavefunction of the impurity bound to the hole. If the strong-coupling wavefunction (27) applies, where |ψ I is independent of q, it follows that the TP Zak phase is equivalent to the Zak phase of the hole. Being in the strong-coupling regime requires the impurity to be sufficiently mobile, J t 1,2 (see also Eq.…”
Section: B the Protocolmentioning
confidence: 99%
“…Here |Φ h (q) denotes the wavefunction of a hole excitation at quasimomentum q while |ψ I describes the wavefunction of the impurity bound to the hole. If the strong-coupling wavefunction (27) applies, where |ψ I is independent of q, it follows that the TP Zak phase is equivalent to the Zak phase of the hole. Being in the strong-coupling regime requires the impurity to be sufficiently mobile, J t 1,2 (see also Eq.…”
Section: B the Protocolmentioning
confidence: 99%
“…While the experimental system in [12] features continuous-time non-Hermitian dynamics, an important question is whether topological invariants can also be defined for discrete-time non-unitary dynamics. This is particularly interesting in light of the recent demonstration of topological properties in unitary discrete-time QWs [9,10,26,29,30].…”
mentioning
confidence: 99%
“…Since each phase is characterized by a topological invariants, this step dependency of bands of energy could be used as a method to measure topological invariants, similar to Ref. [23]. Later, in our calculations of topological invariants, we address this possibility.…”
Section: A Hamiltonian and Energymentioning
confidence: 99%
“…In contrast, in Ref. [23], it was shown that if the protocol of the quantum walks is modified to be time dependent (more precisely, position dependent at each step), it will result in a Bloch-oscillating quantum walk which can be used to directly measure topological invariants imprinted as a Berry phase on the quantum state of the particle. The considered protocol for quantum walks in this paper is also Bloch-oscillating [32].…”
Section: A Hamiltonian and Energymentioning
confidence: 99%
See 1 more Smart Citation